The language of journalism: a multi-genre perspective - Smith, Angela and Higgins, Michael (Bloomsbury Academic, 2020)
Introduction -- Broadcast Journalism -- Magazine Journalism -- Newspaper Journalism --- Sports Journalism -- Digital Journalism.
https://katalog.adlr.link/Record/0-1693561875